A generation at risk the global impact of HIV/AIDS on orphans and vulnerable children - Foster, Geoff; Levine, Carol 1934-; Williamson, John 1948- (Cambridge University Press, 2005)
With a Foreword by Desmond Tutu, Generation at Risk brings insightful perspectives from experienced practitioners and researchers on how a better future can be secured for the millions of children who are being orphaned or made vulnerable by HIV/AIDS. The current situation of these children is grim, and while there has been significant action by governments, international organizations, religious bodies, and non-governmental organizations, the vast majority of children made vulnerable by AIDS have not benefited from any assistance beyond their own extended family and community. A Generation at Risk explains in straightforward terms what is required to fill this gap. The book addresses what needs to be done in the areas of education, community mobilization and capacity building, economic strengthening at household and community levels, psychosocial support, and the protection of children and the fulfilment of their rights
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Children of AIDS patients; AIDS (Disease) in children; Orphans / Services for; Children's rights; Psychosoziale Belastung; Waisenkind; Eltern; Kind; HIV-Infektion; Kinderfürsorge; Aufsatzsammlung